The Acceptance Effectiveness Through Accounts Receivable Billing Period Average - Agung Listiadi (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Sensitivity Performance company to economics depend on sold service. Condition of company’s finance always becomes especial reason to a company to develop its effort. One of the source of fund to company is liquefaction of receivable. Not rarely receivable cannot be billed for as according to its due date, which is on finally must be done abolition to receivable. Intention of this research is to know Effectiveness receivable measured, from industrial ACP. The purpose of this research is to measure the level of ACP of companies engaged in household needs and lifestyles that are included in the stock exchange. Benefit of research is known of ACP hence earning is immediately known by receivable effectiveness. Design/methodology/approach: This study used a descriptive research method. Data is the document obtained financial statement for the period of 2021. As for the subjects in this study are companies engaged in household needs and lifestyle, by calculating the ACP based on the financial statements in 2021. Findings: Based on the results of calculations using the ACP formula, the big unknown ACP is below the industry average. This means that the average consumer pays his debts to the company on deadlines faster than the industry average. This means that the ACP period of companies engaged in the household and lifestyle equipment business is in good condition even though they are facing the era of covid 19. Research limitations/implications: The limitation in this study is that calculating ACP can only be done for one entity. Practical implications: The results of this study can be used as a comparison in a cluster of companies engaged in similar fields. Originality/value: The focus of the research is to find ways to calculate the effectiveness of sales on receivables during the COVID-19 pandemic. Paper type: Research paper